Knowledge, Attitude, and Practice on Over-the-counter Drugs among Undergraduate Students of a Tertiary Care Teaching Hospital - Ruchi Shrestha; Mukta Singh Bhandari (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Over-the-counter drugs are those which are safe and effective for the general public to use, without consulting a health care professional. Self-medication with over-the-counter drugs is common among medicine and health science students. This study aimed to assess the knowledge, attitude, and practice on over-the-counter drugs among undergraduate students of a tertiary care teaching hospital. MATERIAL AND METHODS A descriptive cross-sectional study was conducted among ﬁrst and second year undergraduate students from June 2023 to September 2023. Data was collected through self-administered questionnaire and was entered and analyzed in Statistical Package for Social Sciences version 16. Descriptive statistical analysis was carried out to ﬁnd out knowledge, attitude and practice of over the counter drugs. RESULTS Among 352 students, 272 (77.27%) had good knowledge (with mean knowledge score of 7.22±1.43 out of 9) on over the counter drugs. Almost all of the students 350 (99.43%) had a positive attitude toward over the counter drugs use, (with a mean attitude score of 27.55±2.70, out of 40). Only 195 (55.40%) students always read the instructions on the medicine’s label before use. Most commonly used over the counter drugs was antipyretics 264 (75%). CONCLUSION Majority of the students had good knowledge and practice and positive attitude towards over the counter drugs use, however, there were few inappropriate practices. Awareness on proper use of over the counter drugs among students is necessary in medical institutions to prevent the misuse of these drugs.